2014
DOI: 10.1149/06104.0405ecst
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Annealing on Contact Formation and Stability of IGZO TFTs

Abstract: Annealing processes were investigated on Indium-Gallium-ZincOxide (IGZO) thin-film transistors (TFTs). Molybdenum and aluminum were used as contact metals which defined the working source/drain electrodes. Annealing was performed either pre-metal or post-metal deposition, in various gas ambients including air, oxygen, nitrogen, forming gas (5% H2 in N2) and vacuum. Premetal annealing in air ambient resulted in similar I-V characteristics on Mo-contact and Al-contact devices. A postmetal anneal for Mo-contact d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…[33][34][35][36] In addition, a thermal treatment at such comparatively low temperatures is fully compatible to flexible-and glass substrates and minimizes the risk for inter-diffusion processes of metallic species at the interfaces between the a-IGZO channel and the metallic source and drain contacts, which are known to result in deteriorated TFT performance. [33,[37][38][39] Consequently, the maximum temperature to functionalize the HZO film is limited to 350 °C in the present processing scheme. Therefore, tailoring the HZO film to meet the thermal budget limitations defined by a-IGZO is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] In addition, a thermal treatment at such comparatively low temperatures is fully compatible to flexible-and glass substrates and minimizes the risk for inter-diffusion processes of metallic species at the interfaces between the a-IGZO channel and the metallic source and drain contacts, which are known to result in deteriorated TFT performance. [33,[37][38][39] Consequently, the maximum temperature to functionalize the HZO film is limited to 350 °C in the present processing scheme. Therefore, tailoring the HZO film to meet the thermal budget limitations defined by a-IGZO is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of metals was made due to the following considerations: As a rule of thumb, we 24 and others [31][32][33] found that post-metal-deposition annealing is required to reduce oxygen vacancies in the IGZO film. Also, it was reported that post-deposition annealing results in Molybdenum (Mo) being ohmic contact 34 and in platinum (Pt) becoming a Schottky contact 35 . The Al2O3 was chosen as a source insulator as it was found to show the best performance in our e-beam deposition system.…”
Section: Resultsmentioning
confidence: 99%
“…in Molybdenum (Mo) being ohmic contact 34 and in platinum (Pt) becoming a Schottky contact 35 . The Al2O3 was chosen as a source insulator as it was found to show the best performance in our e-beam deposition system.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of details regarding the annealing conditions has been described previously (7). Devices that had back-channel alumina were annealed at 400 °C in air ambient (45% humidity, class 1000 clean room) for 30 min.…”
Section: Methodsmentioning
confidence: 99%